2007
DOI: 10.1128/jcm.00951-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Löwenstein-Jensen Proportion Method, BacT/ALERT 3D System, and Enzymatic Pyrazinamidase Assay for Pyrazinamide Susceptibility Testing of Mycobacterium tuberculosis

Abstract: Pyrazinamide (PZA) is an important first-line antituberculosis drug because of its sterilizing activity against semidormant tubercle bacilli. In spite of its very high in vivo activity, its in vitro activity is not apparent unless an acidic environment is available, which makes PZA susceptibility testing difficult by conventional methods. The present study was, therefore, planned to assess the performance of the colorimetric BacT/ALERT 3D system and compare the results with those from conventional tests, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
(27 reference statements)
2
41
1
Order By: Relevance
“…We repeated analyses to minimize this error. We did not use the Wayne method to assess pyrazinamide activity to determine whether the mutations led to an impairment of pyrazinamidase activity, because at the time we undertook our study this assay was considered less sensitive for diagnosing pyrazinamide resistance (22). Moreover, a large quantity of bacilli is mandatory for this assay, leading to falsely resistant results.…”
Section: Discussionmentioning
confidence: 99%
“…We repeated analyses to minimize this error. We did not use the Wayne method to assess pyrazinamide activity to determine whether the mutations led to an impairment of pyrazinamidase activity, because at the time we undertook our study this assay was considered less sensitive for diagnosing pyrazinamide resistance (22). Moreover, a large quantity of bacilli is mandatory for this assay, leading to falsely resistant results.…”
Section: Discussionmentioning
confidence: 99%
“…Authors showed that 9.5% (16/169) of the PZAresistant strains were determined to be positive to PZase activity testing, indicating that, for these strains, PZA resistance was not caused by the inactivation of PZase but by some other unknown cause(s) [11]. Other studies also detected PZase activity in PZAresistant strains [24,36,37]. Cui Z study showed only 1% (3/260) of the PZA-susceptible strains negative according to the Wayne's assay, probably due to the weak activity of PZase or to the small quantity of MTB, which makes it difficult to observe the Wayne assay color change with the naked eye at 10 days [11].…”
Section: Discussionmentioning
confidence: 99%
“…DST in such liquid media is costly, especially in some regions that do not have enough economic capabilities [20]. Several other DST methods have been developed, including the molecular drug susceptibility test (mDST) based on the detection of a pncA mutation, the PZase activity assay, and colorimetric methods based on a MIC or redox indicator [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The need for rapid methods of the diagnosis and determination of drug susceptibility testing (DST) is very important. While the procedures for DST of the most of the first-line and second-line antituberculosis drugs have been well standardized in both liquid and solid media, the main problem comes with the PZA DST, is the requirement of acidic pH for PZA activity [17]. It also becomes difficult because of the acidic pH of culture medium restricts the growth of organism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of large inoculum sizes results in the release of NH 3 that leads to increased pH and inactivated PZA [15]. The application of various rapid phenotypic methods such as radiometric BACTEC 460, flourimetric Mycobacteria Growth Indicator Tube (MGIT) 960 (Becton Dickinson), ESP Culture System II (Trek Diagnostic Systems, West-lake, OH), and the colorimetric BacT/ALERT 3D system (bioMerieux Inc., Durham, NC), previously designated MB/BACT (Organon Teknika, Boxtels, The Netherlands) has been reported to be very useful for rapid and reliable susceptibility testing of M. tuberculosis isolates [17]. Presently many laboratories performing PZA liquid DST by the non-radiometric, fully automated, continuous-monitoring MGIT 960 system (Becton Dickinson) that gives reliable result with the turnaround time of 15-22 days [18,19].…”
Section: Introductionmentioning
confidence: 99%